A Study on the Emotional Expression of Chinese Image Shaped by Film and Television Culture from the Perspective of Cross-cultural Communication - Yi, Wang; Bexci, Manual Selvarai (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
Against the backdrop of the deepening globalization process, the profound significance of international communication has become increasingly prominent, serving as a crucial channel for cultural exchange and interaction among nations. The rapid development of Internet technology has had a disruptive impact on the traditional information flow model, compelling the film and television industry to actively adapt to this transformation and gradually integrate into the international wave of technological and ideological innovation. In this context, cross-cultural communication, as a product of the globalization trend, has emerged as a core issue that cannot be ignored and has attracted significant attention in contemporary society. As a key medium in the field of cultural communication, Chinese television cultural programs play a vital role. They are not only important carriers of cultural dissemination but also vivid manifestations of specific cultural values and emotional characteristics. Through meticulous planning and content presentation, these programs can effectively establish and strengthen cultural identity among a wide audience, thereby promoting the extensive dissemination and deep penetration of culture. Among the numerous elements constituting television cultural programs, emotional expression is particularly crucial and has gradually drawn extensive attention and research from the academic community. The rich cultural connotations carried by these programs not only build a solid bridge for cross-cultural communication between countries and facilitate communication and exchange among different cultural backgrounds but also play an indispensable role in shaping a nation's international image and enhancing its soft power. In recent years, with the enhancement of China's comprehensive national strength and the significant improvement of its cultural soft power, the influence of Chinese television programs on the international stage has been expanding, becoming an important window for showcasing the charm of Chinese culture. Against this backdrop, emotional expression, as a core issue in the process of cultural transmission, has become increasingly prominent in terms of its research value and practical significance in the field of cross-cultural communication, urgently requiring in-depth exploration and study.